Glaucoma in a Suburban Tertiary Care Hospital in Nigeria - Enock, Malachi Epo (Ophthalmic Research Center, 2010)
PURPOSE: To determine the incidence and contribution of different types of glaucoma to blindness at Irrua Specialist Teaching Hospital, a suburban tertiary care hospital in Edo State, Nigeria. METHODS: Medical records of all new patients with glaucoma who presented to the eye clinic of the hospital from June 2007 to May 2009 were reviewed. RESULTS: Out of a total of 2,742 new patients seen over the study period, 177 (6.5%) subjects had glaucoma which included primary open angle glaucoma (130 cases, 73.4%), juvenile glaucoma (31 patients, 17.5%), secondary glaucoma (10 subjects, 5.6%), congenital glaucoma (3 cases, 1.7%) and primary angle closure glaucoma (3 persons, 1.7%). Of patients with primary open angle glaucoma, 23 (17.7%) were blind based on visual acuity criteria and 67 (51.5%) were blind based on visual field criteria. CONCLUSION: Glaucoma remains a blinding scourge; late presentation, especially in rural areas, is an important factor predisposing to blindness. In this Nigerian population primary open angle glaucoma was the most prevalent subtype of the disease but primary angle closure glaucoma was rare.